Role strain theory: Applicability in understanding developmental experiences of international junior acrobatic gymnasts - Hayman, R.; Polman, R.; Wharton, K.; Borkoles, E. (Science of Gymnastics Journal, 2020)
It is well established that elite sports performers encounter multiple stressors during their careers. However, limited research has specifically investigated developmental, organisational, and competitive transitional experiences of international junior elite athletes. Through the application of Role Strain Theory (RST), this study extended the sport talent development literature by providing key insights into the experiences of five highly successful Great Britain (GB) junior international acrobat gymnasts, aged 14-17. It explored how they simultaneously combined multiple sport, family and educational role demands during their pre-elite to elite transition and coped with these complex demands. Derived themes from semi-structured retrospective interviews identified a presence of chronic, but low level and manageable role strain during all transitional stages, which enabled positive acrobatic development, life satisfaction, physical and mental well-being and educational progress. All reported how severity and regularity of role strain, specifically overload and conflict, at times fluctuated intermittently during the early teenage years. It was at this point when increased role strain was reported to meet family commitments due to increased training and competition schedules. Challenges faced in maintaining healthy and compatible friendships, particularly with peers outside of acrobatics and school settings, were further sources of role strain during this time. Three key factors which regulated role strain were present in all participant narratives: early internalised acrobatic identity, acrobatic specialisation by very young age and social and tangible guidance from teachers and coaches in support of the athletes` holistic development. Potential further research and limitations are discussed.